Republic of Tajikistan : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents key findings of the Joint Staff Assessment of Tajikistan's Poverty Reduction Strategy Paper Progress Report. Macroeconomic management has improved, and some structural reforms have been implemented, but serious institutional weaknesses hinder effective policy implementation. Privatization of a number of hitherto state-owned enterprises and increasing remittances from migrant workers have facilitated the development of private sector activities in the service sector, and thus contributed to a gradual diversification of the sources of growth. Good progress has also been achieved in maintaining the fiscal discipline.